Primer caso de platinosomosis en Colombia : Platynosomum illiciens (Digenea: Dicrocoeliidae) en Felis catus, Turbo, Antioquia (2009)
ABSTRACT: Platinosomosis is a liver disease caused by Digeneans of the genus Platynosomum Looss, 1907, that affects birds and mammals in tropical and subtropical areas. The high incidence of the disease in cats has allowed to obtain detailed information about the life cycle of the parasite, pathogenesis, diagnosis and treatment. In 2002, in Turbo, Antioquia, we detected a cat (Felis catus) with poor body condition, hair loss, extreme thinness, swollen belly and significant symptoms of liver disease. Given the severity of the disease, the cat was euthanized and the autopsy found digeneans from Dicrocoeliidae family in the liver cysts. This paper aims to establish the taxonomic specificity of the parasite and bring forward the case by describing the clinical symptoms. The digenea was identified as Platynosomum illiciens and the clinical signs are typical of this disease, its diagnosis suggests a coprological review with an ultrasound exam. We recommend making a focus study on Turbo Antioquia, considering its wide distribution in the Caribbean region and neighboring countries. This study is the first case of platinosomosis in Colombia.